Prague fatale eaudiobook Bernie gunther series, book 8. - Kerr, Philip (Bernie Gunther Mystery, 2012)
Philip Kerr's thrilling mystery series starring private detective Bernie Gunther has been hailed as "one of the great historical crime series" by Bookmarks Magazine . Set in 1941, Prague Fatale follows Gunther as he investigates a murder at the country estate of his old boss, SD member Reinhard Heydrich. Heydrich was throwing a dinner party for senior German officers when the victim was discovered—the body mysteriously locked in a room from the inside.